(untitled) (Dimensión Empresarial, 2019)
The world economy experienced a systemic financial crisis that resulted from a period of excessive borrowing and lending. The purpose of the research was to understand the credit decision-making process and the information requirements by banks. A survey was conducted among twenty-two Brazilian credit establishments and results showed that the perceived importance and actual frequency of use of resources such as audited accounts, banker´s internal records and loan experience were similar and security was an important issue for small businesses due to the problem of information asymmetry. Keywords: Credit decision-making, information asymmetry, large and small companies JEL: G21-Banks, F65-Finance, G2-Financial Institutions and Service